AKUNTABILITAS PRAKTIK PENGELOLAAN KEUANGAN DESA GAMTALA, HALMAHERA BARAT PROVINSI MALUKU UTARA - Zainuddin, Zainuddin; Ansar, Resmiyati (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2018)
Desa  Gamtala is  a  social  organization which  has  traditional characteristics, so that the accountability of its financial management process is not always supported by proper system and procedure. Although this system was carried out  in simple way, this could be used to manage the asset  of Desa Gamtala properly. To understand the phenomenon of the financial management in Desa Gamtala, this research was aimed to find out: 1) the participants involved in the financial  management  process  in  Desa  Gamtala,  2)  how  the financial management process in Desa Gamtala was carried out, 3) how the participants involved understand and interpret the accountability of the financial management process. This research was conducted by using qualitative method which emphasizes on the description of every perception and habits of the human. The data analysis was conducted in three  steps, such as:  1) Data  Reduction, 2) Data Display, and 3) Verification. The result of this research shows that: 1) The process of financial management  and  its  accountability in  Desa  Gamtala  was involve all people in Desa Gamtala, 2) The accountability of the financial management is carried out consistently 3) Due to the  social capital, especially belief, the participants of Desa Gamtala realize that accounting is an instrument of accountability and transparency in financial management in Desa Gamtala.